2013
DOI: 10.4236/ojrad.2013.31003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tomographic Slice Thickness and Field of View Variation on the Reproduction of Thin Bone Structures for Rapid Prototyping Purposes —An <i>in</i> <i>Vitro</i> Study

Abstract: This study assessed the influence of acquisition parameters of tomographic volumes on the reproduction of thin bone structures for rapid prototyping purposes. Two parameters were investigated: Field of View (FOV) and Slice Thickness (ST). The specimen was comprised of five pairs of 0.6 mm, 1.1 mm, 1.5 mm, 2.0 mm and 2.8 mm thick cortical bone plates. The plates were stuck into utility wax; the first plate of the pair was in vertical position while the second plate was oblique to the first one. Forty-five tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The results show that segmentation accuracy is more dependent on the reconstruction FOV than on the slice thickness. This observation in in agreement with observations found in other phantom studies [12] [47]. Using the high-resolution point cloud to generate the surface meshes may allow the acquisition of image data with more clinical settings, reducing the exposure of the patient to the radiation without a significant loss in model accuracy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results show that segmentation accuracy is more dependent on the reconstruction FOV than on the slice thickness. This observation in in agreement with observations found in other phantom studies [12] [47]. Using the high-resolution point cloud to generate the surface meshes may allow the acquisition of image data with more clinical settings, reducing the exposure of the patient to the radiation without a significant loss in model accuracy.…”
Section: Discussionsupporting
confidence: 90%
“…Image reconstruction with large slice thicknesses is commonly associated with larger model inaccuracies [10][45] [46]. Nevertheless, in a recent study [47] it was demonstrated that alongside with the slice thickness, the FOV also influences the spatial resolution of the scan and the amount of partial volume averaging. The size of the voxel may be more critical than other potential error sources, such as the surface meshing parameters.…”
Section: Image Deconvolutionmentioning
confidence: 99%
“…Moreover, the effects of variation in spacing between slices for the CT data acquired at a particular slice thickness and variation in other parameters are not considered. Meurer et al [19] concluded that the field of view had qualitatively more influence on the quality of 3D reconstructions than slice thickness for thin bone structures. Whyms et al [20] stated that the linear, angular, and volume measurements can be confidently obtained over a range of parameters for the mandible 3D CT models.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the accuracy of the 3D models depends on the geometry of the object [11,19]. However, the reported investigations [11,12,[19][20][21][22] mainly focus on the effects of slice thickness and spacing on the accuracy of the resulting surface models. Only a few studies [19][20][21][22] have been reported that consider other factors, but in a limited manner.…”
Section: Introductionmentioning
confidence: 99%